“A Future in the Past”? Tourism Development, Outport Archaeology, and the Politics of Deindustrialization in Newfoundland and Labrador in the 1990s - Overton, James (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2007)
The fishing industry crisis of the 1990s saw the already precarious economic base of the many towns and small communities further eroded in Newfoundland and Labrador. The situation was made worse by both federal and provincial pursuit of programs of economic liberalization that sought to limit the role of the state in economic and social affairs. As the effects of the crisis were felt, and established state supports were weakened, tourism was embraced by a growing body of local development and heritage organizations as a way of restoring the shattered economic base of many communities. Limited, short-term funding for some tourism-related projects was provided mostly from government programs, largely as a means of politically managing the structural adjustment that was being pursued.This paper examines the role of the state policy in deindustrialization. After discussing the crisis in Newfoundland and Labrador and the promotion of community development in response to that crisis, some of the problems associated with tourism development and “outport archaeologyn” are outlined. Focusing on sustainability and survival, an assessment is made of the role of tourism in dealing with crisis in the once-fishing-dependent communities of Newfoundland and Labrador.